Evaluating Compliance with Traditional Herbal Treatments in Type 2 Diabetes Mellitus Patients - Mufidah, Naili Zahrotun; Murti, Bhisma; Tamtomo, Didik Gunawan (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: The management of diabetes mellitus is often faced with the challenge of adherence to antidiabetic herbs. Poor adherence to diabetes medication increases the risk of complications and death. This study aims to analyze the determinants related to treatment adherence in Type 2 DM patients. Subject and Method: The cross-sectional study was carried out at UPF Yankestrad Dr. Sardjito Tawangmangu Hospital. A total of 201 adult patients with Type 2 DM were selected in this study. The dependent variable is treatment adherence in Type 2 DM patients. The independent variables were education, knowledge, access to health services, family support, income, and side effects of treatment. Data was collected using questionnaires. Data were analyzed by double linearregression. Result: There was a statistically significant positive association between knowledge and medication adherence (b = 0.19; 95% CI = 0.12 to 0.26; p<0.001); access to healthcare (b = 0.37; 95% CI = 0.26 to 0.47 p<0.001); family support (b = 0.29; 95% CI = 0.20 to 0.39; p<0.001); income (b = 0.15; 95% CI = 0.01 to 0.29; p= 0.030); and there was a negative and statistically significant association between adverse events and medication adherence (b = -0.33; 95% CI = -0.49 up to -0.18; p<0.001). The model fit between the independent variables included in the linear multiple regression analysis model together was able to explain the variation in treatment adherence by 67.12% (Adj R-squared= 67.12%). Conclusion: Treatment adherence in Type 2 DM patients is positively related to knowledge, access to services, family support, and income. The independent variables included in the linear multiple regression analysis model together were able to explain the variation of treatment adherence by 67.12% (Adj R-squared = 67.12%).